THE EFFECTIVENESS OF GROUP COUNSELING WITH SELF-MANAGEMENT TECHNIQUES IN REDUCING STUDENTS' ACADEMIC PROCRASTINATION AT YA BAKII 1 JUNIOR HIGH SCHOOL, KESUGIHAN - Isvi Salsabila (PT. Cadas Insan Madani, 2026)
Academic procrastination is one of the most common problems experienced by students and may negatively affect academic achievement, learning discipline, and responsibility in completing school assignments. This study aimed to examine the effectiveness of group counseling with self-management techniques in reducing students' academic procrastination at Ya BAKII 1 Junior High School, Kesugihan. The study employed a quantitative approach using a pre-experimental method with a one-group pretest-posttest design. The participants consisted of students who demonstrated moderate to high levels of academic procrastination and were selected through purposive sampling. Data were collected using an academic procrastination questionnaire administered before and after the intervention. The treatment was implemented through several group counseling sessions incorporating self-management techniques, including self-monitoring, self-evaluation, self-reinforcement, and self-control. The collected data were analyzed using descriptive statistics and a paired sample t-test to determine differences between pretest and posttest scores. The findings indicated a significant reduction in students' academic procrastination after participating in group counseling sessions using self-management techniques, as evidenced by the lower posttest scores compared to the pretest scores and a significance level of p < 0.05. These results demonstrate that group counseling with self-management techniques is effective in reducing students' academic procrastination. Therefore, school counselors are encouraged to implement self-management-based group counseling programs as an intervention strategy to improve students' academic discipline and responsibility.